Transformasi Digital Administrasi Kepegawaian UIN Ar-Raniry Banda Aceh: Pengembangan Sistem Presensi Berbasis Web Menggunakan Metode Agile - Dewi, Sarini Vita; Faruki, Arvit; Akram, Muhammad (CYBERSPACE: Jurnal Pendidikan Teknologi Informasi, 2026)
Digital transformation in personnel administration has become an urgent need in public higher education institutions, including at UIN Ar-Raniry Banda Aceh. This study aims to develop a web-based employee attendance system that can improve the efficiency, accuracy, and transparency of attendance recording and personnel administration processes. The research was conducted using the Human-Centered Design (HCD) approach and the Agile development method. The system was built using Java with the Spring Boot framework on the back-end, MongoDB as the database, and React.js on the front-end. The development focuses on three types of users: lecturers, permanent lecturers, and educational staff, with specific attention to different attendance location rules. The developed system includes several key features, namely GPS-based check-in and check-out attendance, an online application for leave and official duty, a finance menu that displays details of basic salary, net salary, deductions, remuneration, and meal allowance, as well as an interactive organizational structure visualization feature. All features were designed based on direct user feedback through an iterative HCD process. The development results show that the system is able to overcome the problems of manual attendance that have occurred so far and provides better transparency in personnel data management. This system is expected to serve as an initial step toward digital transformation of personnel administration at UIN Ar-Raniry Banda Aceh and can be replicated in other higher education institutions.